Identification of QTLs for niacin concentration in maize kernels. (23rd April 2019) - Wang, Xu; Zhang, Jing; Dong, Erfei; Mei, Xiupeng; Liu, Chaoxian; Zhou, Lian; Cai, Yilin
Abstract: A genetically induced increase in the niacin concentration of maize kernels is important for the improvement of kernels nutrition. In this paper, the correlation, heredity and variation of free niacin concentration and total niacin concentration in maize kernels were analysed. The results showed that a low or moderate correlation existed between free niacin concentration and total niacin concentration, and that the heritabilities of the two traits were approximately 70%. Quantitative trait loci (QTL) analysis showed that qFNA4a‐HC and qTNA4a‐HC were detected to have a common marker, umc1294 (Bin4.02), in different populations. In population A, qFNA8b and qTNA8a were detected in two generations or two sites, qTNA8c‐F2 and qFNA8b‐HC have a common interval. These QTLs explained 9.7%–17.3% of phenotypic variation. In population B, qFNA4a, explaining 9.3%–11.2% of phenotypic variation, was detected in two environments. Two marker intervals, umc1294‐bnlg490 (Bin4.02‐4.03) and umc1959‐umc1562 (Bin8.05), harbored the QTL for free niacin concentration and total niacin concentration. Furthermore, among a total of 78 QTLs obtained from all datasets, 19, 9 and 9 QTLs were located in Bin8.05‐8.06, Bin4.02‐4.04 and Bin10.01‐10.03, respectively.